A Review of Temporal Bone CT Imaging With Respect to Pediatric Bone-anchored Hearing Aid Placement. Issue 9 (October 2016) - Baker, Aaron; Fanelli, David; Kanekar, Sangam; Isildak, Huseyin
Abstract : Objective: Bone-anchored hearing aid has been shown to be effective in hearing rehabilitation for conductive loss or single-sided deafness. Current FDA guidelines allow implantation in patients over 5 years old. This guideline is at least partially due to concern for thickness of bone stock at the implant site. We aim to investigate whether temporal bone thickness should be a deterrent to implantation in those younger than five. Study Design: A retrospective review of high-resolution temporal bone computed tomographies (CTs) comparing measurements between ears with chronic disease and controls. Setting: Single institution tertiary care center. Patients: One hundred patients between 1 and 5.99 years had temporal bone CTs performed between 2000 and 2009. Patients with chronic ear disease were identified by ICD-9 code, as well as confirmation by review of the imaging. Intervention(s): None. Main Outcome Measures: Temporal bone thickness was measured on axial CT slices at a point 1 cm posterior to the sigmoid sinus, at the superior margin of the bony canal. Results: Average thickness was greater than 3 mm in all age groups. No significant difference was found between age groups, or between normal ears and ears with chronic disease (3.5 mm versus 3.3 mm, p = 0.21) when compared individually. Conclusion: This data shows pediatric temporal bone thickness is frequently greater than the recommended 3 mm, even in patients as young as one. Anatomically, concerns regarding temporal bone thickness in patients younger than five could be reliably addressed with imaging typically obtained in workup of hearing loss.